The Effect of Skincare Review Content on Fulfilling Information Needs on Youtube Channels - Lestari, Anggita; Melinda, Denay; Putri, Shinta Hartini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Beauty Vlogger is a content creator who provides beauty information to his audience, usually beauty vlooger reviews a beauty product and also recommends a skincare product. One of the beauty vloggers who likes to review beauty products is Mary Angline. Mary Angline often makes videos with a beauty theme, namely with video content reviewing beauty products, one of which is skincare to fulfill the information needs of her audience, viewers who watch Mary Angline's content also comment. This study aims to determine the effect of skincare review content on meeting the information needs of commentators on the video "Under 50rb! Rating The Originote (acne prone & oily comby)". This study uses two variables, namely review content with sub-variables of message, message attractiveness, towards fulfilling commentators' information needs, cognitive needs, affective needs, integrative personal needs, integrative social needs, release needs. The theory used is the theory of uses and gratifications. The research method used is a quantitative research method with an explanatory study. The measurement scale used is a Likert scale. The research was conducted on respondents who were commentators on the video "Under 50k! Rating The Originote (acne prone & oily comby)" with a sample size of 123 people based on the slovin formula with an error tolerance of 5%. The result of this study is that there is an effect of skincare review content on fulfilling the information needs of commentators on the video "Under 50k! Rating The Originote (acne prone & oily comby)" with a large influence of 59.5%. The review content factor that most influences the fulfillment of commentators' information needs is the visual influence on cognitive needs with a t value (13.877) > t table (1.980).